Blocking the P2X7 Receptor Improves Outcomes After Axonal Fusion - Rodriguez-Feo, Charles L. (2013)
BACKGROUND: Activation of the P2X7 Receptor on nerve cells causes the formation of pannexin pores, which allows the influx of calcium across the cell membrane. Polyethylene glycol (PEG) and methylene blue (MB) have previously been shown to delay Wallerian degeneration if applied during microsuture repair of the severed nerve. Our hypothesis is that by modulating calcium influx via the P2X7 receptor pathway, we could improve PEG based axonal repair. The P2X7 receptor can be stimulated or inhibited using bzATP or Brilliant Blue (FCF), respectively. METHODS: A single incision rat sciatic nerve injury model was used. The defect was repaired using a previously described PEG, MB fusion protocol. Experimental animals were treated with 100 µL of 100 µM FCF solution (n=8) or 100 µL of a 30 µM bzATP solution (n=6). Control animals received neither FCF, bzATP, nor PEG. Compound Action Potentials (CAPs) were recorded prior to transection (baseline), immediately after repair, and 21 days post operatively. Animals underwent behavioral testing 3,7, 14, and 21 days post operatively. After sacrifice, nerves were fixed, sectioned, and immunostained to allow for counting of total axons. RESULTS: Rats treated with FCF showed an improvement as compared to control at all time points (n=8) (p= .047, .044, .014, and .0059 respectively). A statistical difference was also shown between FCF and bzATP at Day 7 (p<.05), but not shown with days 3, 14, and 21. (p>.05). CONCLUSIONS: Blocking the P2X7 receptor improves functional outcomes after PEG mediated axonal fusion.